New methodology for estimating the burden of infectious diseases in Europe - Kretzschmar, M.; Mangen, M.J.; Pinheiro, P.; Jahn, B.; Fèvre, Eric M.; Longhi, S.; Lai, T.; Havelaar, A.H.; Stein, C.; Cassini, A.; Kramarz, P. (Public Library of Science, 2012)
The Policy Forum allows health policy makers around the world to discuss challenges